THE ROLE OF DIGITAL TECHNOLOGIES IN AGRICULTURE - Rustamjon Rakhimov (American Journals Publishing, 2025)
Digital agriculture is fundamentally transforming farming and helping to reduce poverty in rural areas, which is particularly important for developing countries. Innovations driving these changes include blockchain, artificial intelligence (AI), precision agriculture, automation, livestock technologies, indoor vertical farming, and other advanced technologies. Mobile devices further enhance efficiency and accessibility. Digital agriculture offers numerous benefits: improved monitoring and observation, optimized decision-making, effective communication, time and cost savings, enhanced operational efficiency through specialized software, as well as increased productivity and income.
Keywords: Digital agriculture, sensors, robotics, drones, blockchain